The Death Receptor 3–TNF-like protein 1A pathway drives adverse bone pathology in inflammatory arthritis - Bull, Melanie Jane (The Rockefeller University Press, 2008)
Rheumatoid arthritis (RA) is a chronic inflammatory disease of synovial joints that is associated with cartilage and bone destruction. Death Receptor 3 (DR3), a tumor necrosis factor (TNF) receptor superfamily member, has recently been associated with the pathogenesis of RA. We demonstrate that absence of DR3 confers resistance to the development of adverse bone pathology in experimental antigen-induced arthritis (AIA). DR3(ko) mice exhibited a reduction in all histopathological hallmarks of AIA but, in particular, failed to develop subchondral bone erosions and were completely protected from this characteristic of AIA. In contrast, TNF-like protein 1A (TL1A), the ligand for DR3, exacerbated disease in a dose- and DR3-dependent fashion. Analysis of osteoclast number within AIA joint revealed a reduction in areas susceptible to bone erosion in DR3(ko) mice, whereas in vitro osteoclastogenesis assays showed that TL1A could directly promote osteoclastogenesis in mouse and man. Treatment with antagonistic anti-TL1A mAb protected animals in a systemic model of RA disease collagen-induced arthritis. We therefore conclude that the DR3–TL1A pathway regulates joint destruction in two murine models of arthritis and represents a potential novel target for therapeutic intervention in inflammatory joint disease.